Outcomes of MyoRing Implantation in Eyes with Keratoconus in the Eastern Province of Saudi Arabia: “A Single-Arm Cohort Study” - Yousef Saad Alshammari; Abdulaziz Ismail Al Somali (Journal of Ophthalmology)
Purpose. To evaluate the efficacy and safety of MyoRing implantation in eyes with keratoconus managed at a tertiary eye hospital in the Eastern Province of Saudi Arabia. Methods. This one-armed historical cohort study included keratoconus patients operated for MyoRing implant. The cases were assessed before and 6 months after surgery. Uncorrected visual acuity (UCVA) and best-corrected visual acuity (BCVA), spherical equivalent (SE), central corneal thickness (CCT), and corneal curvature (Kmean) were noted and measured before and 6 months after the intervention. Intra- and postoperative complications were noted. Result. We studied 12 eyes of 12 patients with moderate keratoconus. The median of Kmean was 50.6 mm (IQR 47.54; 52.5) and 44.5 mm (IQR 42.5; 46.8) before and 6 months after surgery. The change in Kmean was significant (P=0.002). The median spherical equivalent (SE) was −5.1D (interquartile range (IQR) 7.1; −3.6) and −0.6 (IQR −2.1; 0.8) before and 6 months after surgery. The difference in SE was significant (Wilcoxon signed-rank test P=0.004). The CCT was 447 ± 34 μm and 444 ± 30 μm before and 6 months after surgery, respectively. The CCT change was not significant (P=0.26). The UCVA and BCVA improved by 2 or more lines in 9 (75%) eyes, remained stable in 2 (16.7%) eyes, and decreased in 2 (16.7%) eyes. Conclusion. MyoRing implant seems to be a safe and effective procedure to manage low and moderate keratoconus. The outcomes could be further enhanced by additional procedures such as collagen cross-linkage and photorefractive keratectomy if warranted.